Pompeii as a Pottery Production centre: An archaeometric approach - Schneider, Gerwulf; Daszkiewicz, Małgorzata; Cottica, Daniela (Rei Cretariae Romanae Fautorum Acta, 2024)
Recently a new project of archaeometric investigation focused on pottery production and circulation at Pompeii was undertaken in cooperation between University of Venice Ca’ Foscari, the laboratory of ARCHEA in Warsaw and the Free University of Berlin. The project aimed to give a scientific description and interpretation to a number of wares of supposed local and regional production, retrieved during recent stratigraphic excavations undertaken in Regio Vi, insulae 7 and 14 and by past excavations (1980–1981) carried out in the western part of the forum at Pompeii.